Periodontal Care Needs In Diabetic Patients: A Study Of The Prolanis Group In Banjarbaru City - Naning Kisworo Utami; Metty Amperawati; Rasuna Ulfah; Bunga Nurwati; Hammad (Jurnal Penelitian Pendidikan IPA, 2024)
South Kalimantan has seen a significant rise in dental and oral health issues, particularly periodontal diseases, which are prevalent among diabetic patients. This research aimed to analyze the periodontal status and the corresponding treatment needs of the Prolanis group, consisting of diabetic mellitus (DM) patients, at Sungai Ulin Health Center and South Banjarbaru Health Center, Banjarbaru City, during the second year of the study. A descriptive-analytical approach was employed to assess the periodontal tissue condition using the Community Periodontal Index of Treatment Needs (CPITN). A total of 65 respondents were examined, and the results indicated that 49.23% of the participants had tartar, while 30.78% displayed healthy periodontal conditions. Counseling on oral hygiene and scaling treatments were provided. The study emphasizes the importance of regular dental check-ups and proper oral hygiene practices, particularly in diabetic patients, to prevent further complications. Recommendations include brushing teeth twice daily and reducing the intake of cariogenic foods.